One-pot MCDA-CRISPR-Cas-based detection platform for point-of-care testing of severe acute respiratory syndrome coronavirus 2 - Wang, Xiaoxia; Yang, Rui; Tang, Tian; Zhou, Yuzhen; Chen, Heng; Jiang, Yihao; Zhang, Shirong; Qin, Sihan; Wang, Meijuan; Wang, Chuan (Frontiers in Microbiology, 2024)
Compared to quantitative real-time PCR (q-PCR), CRISPR-Cas-mediated technology is more suitable for point-of-care testing (POCT) and has potential for wider application in the future. Generally, the operational procedure of CRISPR-Cas-mediated diagnostic method consists of two independent steps, the reaction of signal amplification and the CRISPR-Cas-mediated signal detection. Complex multi-step procedures can easily lead to cross-contamination. To develop a convenient and rapid method for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) detection, we propose a MCTOP method (Multiple cross displacement amplification-CRISPR-Cas12b-based testing in one-pot), which targets the open reading frame 1ab (ORF1ab) and nucleocapsid protein (N) gene of SARS-CoV-2. This method combines MCDA isothermal amplification and CRISPR-Cas-mediated sequence-specific detection into a one-pot reaction. The optimal reaction was achieved with isothermal amplification of 40 min and CRISPR-Cas-based detection of 15 min, both at 64°C. Then, the results can be visualized by the real-time fluorescence instrument and also lateral flow biosensor. The lowest detection limit of the proposed method is 10 copies of each of target sequences, and it has no cross-reactivity with non-SARS-CoV-2 templates. In a clinical test of 70 pharyngeal swab samples, MCTOP assay showed a specificity of 100% and sensitivities of 98 and 96% for the real-time fluorescence instrument and lateral flow biosensor, respectively. The MCTOP developed in this study is a rapid, convenient, highly sensitive, and specific method for SARS-CoV-2 nucleic acid detection. It can be used as an effective point-of-care testing (POCT) tool for clinical diagnosis and epidemiologic surveillance of SARS-CoV-2 infections, especially suitable for the basic, field and clinical laboratory.